A correlated multi-observable assessment for vanadium redox flow battery state of charge estimation : empirical correlations and temperature dependencies - Niklas Janshen and Simon Ressel and Antonio Chica and Thorsten Struckmann (Electrochimica acta, 2024)
The efficient operation of vanadium redox flow batteries requires the half cell specific monitoring of the state of charge (SOC). Monitoring of the SOC is affected by temperature fluctuations, which need to be distinguished from the SOC signal. Several SOC monitoring approaches have been proposed in the literature and either been evaluated individually or compared to one other approach. The aim of this study is to contribute to SOC sensor development for VRFB by providing a first correlated assessment of several established and new SOC monitoring methods. We perform multi observable measurements of: half cell electrolyte potentials, electrolyte densities, electrolyte volumes, electrolyte viscosity related pressure drops, pH related potentials and UV/Vis absorbances. We determine SOC correlations of these observables in full charge/discharge cycles at constant temperature and derive temperature corrections in additional measurements over a range of 12 °C to 32 °C at 25 %, 50 % and 75 % SOC. We compare the SOC and temperature sensitivity as well as the accuracy of these monitoring methods at constant and varied temperature. We find that the established half cell electrolyte potentials and UV/Vis absorbances can estimate the SOC at constant temperature with measurement errors of 1.7% and 4%, respectively and with slightly higher errors at varying temperatures. The viscosity related pressure drop and electrolyte density are both suitable for SOC estimation if temperature corrections are included. The pH related potentials for the positive half cell and both half cell electrolyte volumes could be used for a rough SOC estimate, but need accurate temperature corrections and further long term stability evaluation.
Keywords: State of charge; Temperature correlation; Vanadium redox flow battery